2020
DOI: 10.3390/ijerph17030969
|View full text |Cite
|
Sign up to set email alerts
|

Geoacumulation of Heavy Metals in Sediment of the Fluvial–Lagoon–Deltaic System of the Palizada River, Campeche, Mexico

Abstract: The fluvial–lagoon–deltaic system of the Palizada River in Campeche is an ecosystem of socioeconomic and ecological importance. It is justifiable to carry out studies in this system due to its connection with another larger ecosystem called the Términos Lagoon. The objective of this investigation was to analyze the concentration of Pb and Cd in sediments of the fluvial–lagoon–deltaic system of the Palizada River and to determine, with this, the contamination index of these metals. Cd showed the highest concent… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 49 publications
0
4
0
Order By: Relevance
“…In addition, the results of the pollution indices tested in the present study indicate the existence of temporal and spatial fluctuations regarding the pollution level with certain heavy metals, due to the presence of pollution sources, heavy metal mobility, sediment characteristics, sediment transport, the hydro-morphological profile of the river and climatic conditions [61].…”
Section: Discussionmentioning
confidence: 57%
“…In addition, the results of the pollution indices tested in the present study indicate the existence of temporal and spatial fluctuations regarding the pollution level with certain heavy metals, due to the presence of pollution sources, heavy metal mobility, sediment characteristics, sediment transport, the hydro-morphological profile of the river and climatic conditions [61].…”
Section: Discussionmentioning
confidence: 57%
“…Environmental studies on coastal lagoons and marine estuaries are of considerable importance because these environments are characterized by complex biogeochemical processes. In particular, sediments can become sinks for pollutants (including heavy metals and pesticides), and play a key role in contaminant remobilization in aquatic systems under favorable conditions (Navarrete-Rodríguez et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…In Mexico, groundwater supplies 75% of drinking water. Several studies have shown that Mexican aquifers and adjacent soils contain high concentrations of heavy metals (Armienta & Segovia 2008;Maldonado et al 2008;Pastrana-Corral et al 2017;Navarrete-Rodríguez et al 2020). Heavy metals and other hazardous elements are naturally present in the environment as minerals, but human activities release them into the environment.…”
Section: Introductionmentioning
confidence: 99%